Basic College Mathematics (9th Edition)

Published by Pearson
ISBN 10: 0321825535
ISBN 13: 978-0-32182-553-7

Chapter 9 - Basic Algebra - 9.4 Order of Operations - 9.4 Exercises: 18

Answer

73

Work Step by Step

$(-5)^{2}$+ $(-6)^{2}$+ 12 Step 1 : Apply the exponents : $(-5)^{2}$ = -5 * -5 = 25 and $(-6)^{2}$=-6* -6=36 25 + 36 + 12 Step 2: Addition from left to right 25 + 36 = 61 Now add 61 + 12 = 73
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.